2019
DOI: 10.1136/bmjopen-2019-028929
|View full text |Cite|
|
Sign up to set email alerts
|

Recorded poor insight as a predictor of service use outcomes: cohort study of patients with first-episode psychosis in a large mental healthcare database

Abstract: ObjectivesTo investigate recorded poor insight in relation to mental health and service use outcomes in a cohort with first-episode psychosis.DesignWe developed a natural language processing algorithm to ascertain statements of poor or diminished insight and tested this in a cohort of patients with first-episode psychosis.SettingThe clinical record text at the South London and Maudsley National Health Service Trust in the UK was used.ParticipantsWe applied the algorithm to characterise a cohort of 2026 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…The final sample comprised 3350 patients of predominantly male gender (n=2077, 62%). Median (IQR) age was 24 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). White (n=1037), black-other (n=847) and black-Caribbean (n=635) were the most frequently represented ethnic groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final sample comprised 3350 patients of predominantly male gender (n=2077, 62%). Median (IQR) age was 24 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). White (n=1037), black-other (n=847) and black-Caribbean (n=635) were the most frequently represented ethnic groups.…”
Section: Resultsmentioning
confidence: 99%
“…24 These techniques use machine learning to learn from human-annotated examples and are able to navigate term negation (eg, 'No thought disorder elicited') and mentions irrelevant to that which is being measured (eg, 'His father has thought disorder'). This approach has previously been used to investigate transdiagnostic risk for psychosis, 25 the association of negative symptoms with antipsychotic treatment failure, 26 poor insight as a predictor of service use outcomes 27 and the association of cannabis use with hospital admissions 28 in people with psychotic disorders. Our sample of 3350 patients represents the largest known sample in this field to date.…”
Section: Introductionmentioning
confidence: 99%
“…However, some research suggests an insight paradox, wherein better insight is associated with worse outcomes. For example, better insight is linked to greater depression ( Lysaker et al, 2007 ; Ramu et al, 2019 ; Tariku et al, 2019 ), but this is inconsistently observed ( Arraras et al, 2019 ; Konsztowicz and Lepage, 2019 ). Relatedly, increased suicidality and attempts are sometimes ( Ozturk et al, 2018 ; Villa et al, 2018 ), but not always ( Ayesa-Arriola et al, 2018 ) associated with better insight.…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of illness as a predictor of a more favorable outcome in first‐episode psychosis has been evaluated in research studies 32,33 . Moreover, the significance of relationships and mental differentiation in the early stages of recovery was recently supported by research findings by Bourdeau et al 16 who followed 49 patients with early psychosis and found a very significant increase in social engagement, narrative development, and occupation between the moratorium and awareness stages of recovery.…”
Section: Threshold From Moratorium To Awarenessmentioning
confidence: 99%